Mothers know best: Maternal signaling boosts larval resilience under ocean acidification conditions - Emma Timmins-Schiffman; Larken Root; Ryan Crim; Mollie A. Middleton; Megan M. Ewing; Jacob Winnikoff; Gracelyn Ham; Giles Goetz; Steven Roberts; Mackenzie R. Gavery (Aquaculture, 2026)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Ontogenetic changes in embryonic and brain gene expression in progeny produced from migratory and resident O ncorhynchus mykiss - Garrett J. McKinney; Matthew C. Hale; Giles Goetz; Michael Gribskov; Frank P. Thrower; Krista M. Nichols (Molecular Ecology, 2015)
Little information has been gathered regarding the ontogenetic changes that contribute to differentiation between resident and migrant individuals, particularly before the onset of gross morphological and physiological changes in migratory individuals. The aim of this study was to evaluate gene expression during early development in Oncorhynchus mykiss populations with different life histories, in a tissue known to integrate environmental cues to regulate complex developmental processes and behaviours. We sampled offspring produced from migrant and resident parents, collecting whole embryos prior to the beginning of first feeding, and brain tissue at three additional time points over the first year of development. RNA sequencing for 32 individuals generated a reference transcriptome of 30 177 genes that passed count thresholds. Differential gene expression between migrant and resident offspring was observed for 1982 genes. The greatest number of differentially expressed genes occurred at 8 months of age, in the spring a full year before the obvious physiological transformation from stream‐dwelling parr to sea water‐adaptable smolts begins for migrant individuals. Sex and age exhibited considerable effects on differential gene expression between migrants and resident offspring. Differential gene expression was observed in genes previously associated with migration, but also in genes previously unassociated with early life history divergence. Pathway analysis revealed coordinated differential expression in genes related to phototransduction, which could modulate photoperiod responsiveness and variation in circadian rhythms. The role for early differentiation in light sensitivity and biological rhythms is particularly intriguing in understanding early brain processes involved in differentiation of migratory and resident life history types.

Differential gene expression associated with dietary methylmercury (MeHg) exposure in rainbow trout (Oncorhynchus mykiss) and zebrafish (Danio rerio) - Qing Liu; Niladri Basu; Giles Goetz; Nan Jiang; Reinhold J. Hutz; Peter J. Tonellato; Michael J. Carvan (Ecotoxicology, 2013)

A genetic basis for the phenotypic differentiation between siscowet and lean lake trout ( Salvelinus namaycush ) - FREDERICK GOETZ; DANIEL ROSAUER; SHAWN SITAR; GILES GOETZ; CRYSTAL SIMCHICK; STEVEN ROBERTS; RONALD JOHNSON; CHERYL MURPHY; CHARLES R. BRONTE; SIMON MACKENZIE (Molecular Ecology, 2010)
In Lake Superior there are three principal forms of lake trout ( Salvelinus namaycush ): lean, siscowet and humper. Wild lean and siscowet differ in the shape and relative size of the head, size of the fins, location and size of the eyes, caudal peduncle shape and lipid content of the musculature. To investigate the basis for these phenotypic differences, lean and siscowet lake trout, derived from gametes of wild populations in Lake Superior, were reared communally under identical environmental conditions for 2.5 years. Fish were analysed for growth, morphometry and lipid content, and differences in liver transcriptomics were investigated using Roche 454 GS‐FLX pyrosequencing. The results demonstrate that key phenotypic differences between wild lean and siscowet lake trout such as condition factor, morphometry and lipid levels, persist in these two forms when reared in the laboratory under identical environmental conditions. This strongly suggests that these differences are genetic and not a result of environmental plasticity. Transcriptomic analysis involving the comparison of hepatic gene frequencies (RNA‐seq) and expression (quantitative reverse transcription–polymerase chain reaction (qPCR)) between the two lake trout forms, indicated two primary gene groups that were differentially expressed; those involving lipid synthesis, metabolism and transport (acyl‐CoA desaturase, acyl‐CoA binding protein, peroxisome proliferator‐activated receptor gamma, and apolipoproteins), and those involved with immunity (complement component C3, proteasome, FK506 binding protein 5 and C1q proteins). The results demonstrate that RNA‐seq can be used to identify differentially expressed genes; however, some discrepancies between RNA‐seq analysis and qPCR indicate that methods for deep sequencing may need to be refined and/or different RNA‐seq platforms utilized.

Analysis of Genes Isolated from Plated Hemocytes of the Pacific Oyster, Crassostreas gigas - Steven Roberts; Giles Goetz; Samuel White; Frederick Goetz (Marine Biotechnology, 2009)